Evaluating the user-experience of existing strategies to limit video game session length - Davies, Bryan (Department of Computer Science, 2019)
Digital video games are an immensely popular form of entertainment. The meaningful positive experiences that games facilitate are fundamental to the activity; players are known to invest a lot of time playing games in search of those experiences. Digital games research is polarized. Some studies find games to be a healthy hobby with positive effects; games promote well-being through regular experience of positive psychological experiences such as flow and positive emotions. Others have identified rare problematic use in those players who devote excessive amounts of time to gaming, associating them with social dysfunction, addiction, and maladaptive aggression. While it remains unclear if games cause these effects, or merely coincide with play, the negative effects historically receive more attention in both popular media and academia. Some authorities attempt to reduce the harms associated with games to such an extent that their methods have become national policy affecting all players including those who exhibit no negative outcomes. In South Korea and Taiwan, policing authorities employ a behaviour policy that sets strict daily limits on session length, thereby controlling the amount of time people spend playing games each day. In China, the General Administration of Press and Publication employ a design policy requiring that games service-providers fatigue their games’ mechanics after a period to coax them to take a break sooner than they ordinarily would. Both policy types alter player interaction with games in any given session and it is unclear how these policies affect players in general. This research aims to compare sessions affected by the behaviour policy, design policy, and policy-free sessions in terms of session length, measurable subjective user-experience, the player's intention to return to the game, and their reasons for choosing to stop playing in a particular session. For use in a repeated-measures experiment, we modified the action RPG Torchlight II to simulate both policies. Participants had one session at the same time each week for three consecutive weeks. In varied sequences, participants played a control session unaffected by policy, a onehour shutdown session representing behaviour policy, and a fatigue session representing design policy. After each session, we recorded their session's length, their user-experience in terms of flow and affect, their intention to return to the game, and their reason for ending the current session. We found that our shutdown condition successfully decreases session length, when compared to the other conditions. The condition facilitates strong flow, moderate positive-affect, and weak negative-affect. The shutdown event does not appear to degrade positive experiences and makes participants slightly more upset (statistically significant) than they would be after choosing to stop playing. This is because players do not get to make that decision, and because players are unable to complete the goals they have set for themselves. Most players intended to play the game again immediately or sometime later in that same day, much sooner (statistically significant) iii Word Template by Friedman & Morgan 2014 than they would after choosing to stop. This also may be due to satisfaction associated with choosing to stop, or being unable to complete their self-set goals. We found that our fatigue condition increases session length when compared to the other conditions. This result contradicts the intentions associated with design policies: shorter sessions. The fatigue mechanics make the game more difficult, which increases the time required for players to complete the goals they have set for themselves, whether it is to complete a level, quest, or narrative sequence. The condition facilitates high levels of flow, moderate positive-affect and low negativeaffect; the condition does not appear to degrade these positive experiences, nor increase negative experience. Most players intended to take the longest breaks between sessions of at least one day, and although we observed that these were longer than the control condition, the differences is not statistically significant. We found that most participants chose to stop playing when the game stopped providing them with positive experiences, or begins to generate discomfort. A large group of participants chose to stop because another activity took priority. Few participants chose to stop because they were satisfied with their session. Less than one third of players explicitly referenced the fatigue mechanics in their decision to stop. Neither policy is holistically better than the other. Both provide strong positive experiences, and have different effects on session length. Whereas it appears that the fatigue condition fails to reduce session length, it also appears that players intend taking longer breaks between sessions, which may reduce total play-time across all sessions. Similarly, the shutdown condition may increase total play time, or at least bring it closer to normal amounts of play-time while also making players more upset. Our operational definition of user-experience is bi-dimensional, and does not include many experiential constructs commonly associated with digital games. During this research, several reliable and valid, and more representative experience measures became available. Any future work on this topic should make use of one of these. Our experiment tested the effects of player experience associated with a single game, genre, and context. Future research should reduce the variation of player factors by focusing on single personalities, typologies, or risk-factors rather than generalizing to all players. We tested out participants only as they played in the early stages of Torchlight II. It is possible that the game's narrative elements, rather than the gameplay mechanics fatigued by the design policy, motivated continued play. We suggest a longitudinal study of the individual policies to explore their effects over many sessions.